Advanced glycation end products‐related modulation of cathepsin L and NF‐κB signalling effectors in retinal pigment epithelium lead to augmented response to TNFα. Issue 1 (19th October 2018) - Sharif, Umar; Mahmud, Nur Musfirah; Kay, Paul; Yang, Yit C.; Harding, Simon P.; Grierson, Ian; Kamalden, Tengku Ain; Jackson, Malcolm J.; Paraoan, Luminita
Abstract: The retinal pigment epithelium (RPE) plays a central role in neuroretinal homoeostasis throughout life. Altered proteolysis and inflammatory processes involving RPE contribute to the pathophysiology of age‐related macular degeneration (AMD), but the link between these remains elusive. We report for the first time the effect of advanced glycation end products (AGE)—known to accumulate on the ageing RPE's underlying Bruch's membrane in situ—on both key lysosomal cathepsins and NF‐κB signalling in RPE. Cathepsin L activity and NF‐κB effector levels decreased significantly following 2‐week AGE exposure. Chemical cathepsin L inhibition also decreased total p65 protein levels, indicating that AGE‐related change of NF‐κB effectors in RPE cells may be modulated by cathepsin L. However, upon TNFα stimulation, AGE‐exposed cells had significantly higher ratio of phospho‐p65(Ser536)/total p65 compared to non‐AGEd controls, with an even higher fold increase than in the presence of cathepsin L inhibition alone. Increased proportion of active p65 indicates an AGE‐related activation of NF‐κB signalling in a higher proportion of cells and/or an enhanced response to TNFα. Thus, NF‐κB signalling modulation in the AGEd environment, partially regulated via cathepsin L, is employed by RPE cells as a protective (para‐inflammatory) mechanism but renders them more responsive to pro‐inflammatory stimuli.